INTRODUCTION OF EDUCATIONAL-PROFESSIONAL BACHELOR PROGRAMME IN THE FIELD OF “PUBLIC MANAGEMENT AND ADMINISTRATION” IN UKRAINE - L.O.Bіelova; D.V., Karamyshev (Pressing Problems of Public Administration, 2016)
The necessity for introduction in Ukraine of a programme for training Bachelors of Public Management and Administration has been substantiated; it has been proved that higher education in the  eld should be provided based on the principle of degree training and on condition that all the components of the education system are well-developed, consistent, and function in a balanced way. An insight has been provided into the essence and speci city of the educational-professional programme for training Bachelors in the field of “Public Management and Administration”